YouTube 'Adpocalypse': The Youtubers' journey from ad-based to patron-based revenues - Raphaela Andres; Michelangelo Rossi; Mark Tremblay (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
In the past decade, the Creator Economy has witnessed unprecedented growth. This dynamic ecosystem thrives on a multi-sided business model, connecting content creators, users, and advertisers. However, matching the needs of different stakeholders is a complex challenge, as evidenced by the impact of the YouTube 'Adpocalypse' in 2017, when major advertisers fled Youtube due to concerns about their ads appearing alongside objectionable content. This paper explores the response by content creators that use both Youtube and Patreon to YouTube's content moderation policies following the 'Adpocalypse'. We find that these content creators shift their efforts toward Patreon which uses a subscription fee model instead of an ad-based model; as a result, consumers subsequently increase their use of Patreon through memberships, comments, and likes. However, we also find that Youtube's content moderation, and the shift by content creators and consumers that follows, results in an increase in toxicity on Patreon.
Keywords: L10; L20; L82; 330; Patreon; Platform Competition; Multi-homing; Content Creators